Autonomia instytucjonalna a podatność struktury administracji w procesie europeizacji prawa administracyjnego - Dominiak, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
In our times action of the public administration in Poland conditioned is not only contents of the native law but also with norms coming from the European law. His influence on our law isn’t raising doubts. The problem concerns only an admissibility and intensities occurring under his effect of changes. Whether shaping structures of the public administration by design being in the management of member states also hatch for transformations? There is no unequivocal answer and the attempt to grant her is involving a penetrating analysis of the regulation of individual fields for her activities.
Keywords: autonomia instytucjonalna; struktura administracji; europeizacja; prawo administracyjne